AGE, EDUCATIONAL LEVEL, ANXIETY LEVEL, AND SLEEP PATTERNS OF CERVICAL CANCER PATIENTS UNDERGOING EXTERNAL RADIOTHERAPY TREATMENT - Hidayah, Hilda Nur; Puspita, Sylvie; Sari, Gevi Melliya; Putra, Kusuma Wijaya Ridi; Sasmito, Nanang Bagus (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Background: Treatment for cervical cancer includes surgery, radiotherapy or chemotherapy. Quite a lot of cancer sufferers who go to hospitals receive radiation therapy. The diagnosis and treatment of cervical cancer is always accompanied by psychological challenges, namely anxiety, which causes sleep pattern disturbances in the patient. Objective: This study aimed to determine the relationship between age, education level, anxiety level, and sleep patterns in cervical cancer patients undergoing external radiotherapy treatment. Method: The research method used a cross sectional approach design by collecting data on independent variables and dependent variables. The sampling technique in this research used Total Sampling. The sample consisted of 20 cervical cancer respondents who underwent external radiation, then the data collected was processed using the Spearmen Rho test. Results: Based on the research results, it was found that only anxiety level was related to sleep pattern (r = .519, p < .05). Meanwhile, age and education level have no relationship with sleep patterns. Conclusion: The anxiety level of cervical cancer patients in facing external radiotherapy treatment can affect their sleep patterns, so understanding is needed by a health worker to reduce the patient's anxiety.